Evaluación de métodos de injertación y edad de varetas en plántulas de Chirimoya (Annona cherimola Mill) bajo invernadero - Labanda Cajamarca, Diego Fernando (2019)
The present study was carried out at the Germplasm Bank, belonging to the National University of Loja. The objective was to determine the percentage of seizure of three grafting methods and the age of rods and the morphological characteristics of cherimoya (Annona cherimola Mill) seedlings grafted under greenhouse. The evaluation period lasted five months, from December 2018 - April 2019, in a period of 30 days. The statistical design used was completely random with 4 treatments and 3 repetitions: terminal spike with previous year's spike, lateral spike with previous year's spike, English spike with previous year's spike and terminal spike with current year's spike. The variables evaluated were: percentage of graft attachment, days at turgidity and bud emergence, number of buds, number of leaves, leaf length, leaf width, petiole length, petiole width, plant height, neck diameter, bud length and bud diameter. As for the results of the morphological characteristics of the grafts, the development of such characteristics were similar there were no significant differences, only in the length of the bud of the terminal and lateral scion graft with reed of the previous year had a better development unlike the other two treatments. In conclusion, the best treatment was the English reed with the previous year, reaching 82.22% of grafted plant succers. Keywords: graft, morphological characteristics, seizure